Pengaruh Disiplin Kerja dan Loyalitas Karyawan terhadap Kinerja Karyawan pada Toko Rahma Tulungagung - Anggy Ferryta Permata Andayani; Muhammad Anasrulloh (Journal on Education, 2024)
This study aims to quantitatively describe the effect of work discipline and employee loyalty on employee performance at Rahma Tulungagung Store both partially and simultaneously. The population in this study were employees of Rahma Tulungagung Store with a sample of 73 respondents with saturated sampling technique. Data collection in this study used a questionnaire, with a Likert scale. After that, the instrument test and the classical assumption test consisting of normality test, linearity test, multicollinearity test, and heteroscedasticity test were carried out. The data analysis method uses multiple linear regression analysis, hypothesis testing and the coefficient of determination with the help of the SPSS Version 21 for windows program. The test results show that Work Discipline and Employee Loyalty affect Employee Performance at Rahma Tulungagung Store both partially and simultaneously. The results of this study can be used for employee policy making suggestions at Rahma Tulungagung Store.